TEACHING ENGLISH FOR SPECIFIC PURPOSES TO STUDENT NURSES - Nurmainiati Nurmainiati (Universitas Syiah Kuala, 2015)
This research is about Teaching English for Specific Purposes [ESP] to student nurses at an academy in Banda Aceh. It is an evaluative descriptive study that describes preparations by the lecturer, the teaching techniques used, the teaching activities, the teaching materials and resources, and the assessment of the students’ achievements. The subjects of this research were the English lecturer and all the third semester students at the academy. The instruments used for collecting data were observations, interviews, and document analysis of the English lecturer’s syllabus and lesson plan. The findings of this research are in three parts. The findings from the observation concerned on (a) the syllabus and lesson plan, (b) the materials and learning resources, and (c) the scheduling of the lessons. The findings from the interviews were on (a) the academic administrator who did not ask the English lecturer to prepare lesson plans before starting the lessons, and (b) the English lessons were focused only on speaking. Finally, the findings from the document analysis were on (a) the English syllabus that did not fully cover the subjects as set-out in the curriculum, and (b) the assessment of achievements of the students was well done by the English lecturer.